Hydroxyapatite Thin Films of Marine Origin as Sustainable Candidates for Dental Implants - Gabriela Dorcioman; Valentina Grumezescu; George E. Stan; Mariana Carmen Chifiriuc; Gratiela Pircalabioru Gradisteanu; Florin Miculescu; Elena Matei; Gianina Popescu-Pelin; Irina Zgura; Valentin Craciun; Faik Nüzhet Oktar; Liviu Duta (MDPI AG, 2023)
Novel biomaterials with promising bone regeneration potential, derived from rich, renewable, and cheap sources, are reported. Thus, thin films were synthesized from marine-derived (i.e., from fish bones and seashells) hydroxyapatite (MdHA) by pulsed laser deposition (PLD) technique. Besides the physical-chemical and mechanical investigations, the deposited thin films were also evaluated in vitro using dedicated cytocompatibility and antimicrobial assays. The morphological examination of MdHA films revealed the fabrication of rough surfaces, which were shown to favor good cell adhesion, and furthermore could foster the in-situ anchorage of implants. The strong hydrophilic behavior of the thin films was evidenced by contact angle (CA) measurements, with values in the range of 15-18°. The inferred bonding strength adherence values were superior (i.e., ~49 MPa) to the threshold established by ISO regulation for high-load implant coatings. After immersion in biological fluids, the growth of an apatite-based layer was noted, which indicated the good mineralization capacity of the MdHA films. All PLD films exhibited low cytotoxicity on osteoblast, fibroblast, and epithelial cells. Moreover, a persistent protective effect against bacterial and fungal colonization (i.e., 1- to 3-log reduction of E. coli, E. faecalis, and C. albicans growth) was demonstrated after 48 h of incubation, with respect to the Ti control. The good cytocompatibility and effective antimicrobial activity, along with the reduced fabrication costs from sustainable sources (available in large quantities), should, therefore, recommend the MdHA materials proposed herein as innovative and viable solutions for the development of novel coatings for metallic dental implants.